2020
DOI: 10.1590/1516-3180.2019.0325.r1.06112019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence study on self-declared work accidents in areas covered by family health strategies: a cross-sectional study

Abstract: Occupational accidents are a complex phenomenon and a major public health problem that requires attention from all sectors, including healthcare, industry or services, because these accidents generate high socioeconomic costs. 1 Work that is carried out under unsuitable conditions can cause various adverse consequences for humans, both physically and psychologically. These consequences may give rise to impairments that lead to absenteeism, premature retirement, reduced income, job disruption for the family, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The results showed that occupational accidents have a positive and direct effect on work-family conflict. These results are in line with the findings of Pereira et al [22], Osca and Lopez [23], Malakoutikhah et al [24], and Jamshidian et al [25]. Occupational accidents lead to mental imbalance and psychological trauma in nurses, and this stress can be drawn in the process of the mechanism of transfer to the work-family environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that occupational accidents have a positive and direct effect on work-family conflict. These results are in line with the findings of Pereira et al [22], Osca and Lopez [23], Malakoutikhah et al [24], and Jamshidian et al [25]. Occupational accidents lead to mental imbalance and psychological trauma in nurses, and this stress can be drawn in the process of the mechanism of transfer to the work-family environment.…”
Section: Discussionsupporting
confidence: 91%
“…A literature review shows that no research has been conducted to investigate the relationship between occupational accidents and quality of work-life mediated by work-family conflict in ER nurses. But the results of this study on the relationship between occupational accidents and work-family conflict [22,23] and occupational accidents with quality of worklife [26,27] and finally, work-family conflict is consistent with the quality of work-life [28][29][30]. Work-related accidents alone can impair the quality of work-life.…”
Section: Discussionmentioning
confidence: 94%